POPULAR MUSIC OF THE GREEK WORLD: A NOTE FROM THE ORGANISERS. (December 2020) - Beaton, Roderick; Bennet, John; Kallimopoulou, Eleni; Poulos, Panagiotis; Williams, Chris
Abstract : In May 2019 the British School at Athens hosted an international conference on popular music of the Greek world. The conference aimed to explore and evaluate the diversity of Greek music apparent in the rich variety of local traditions and in the richness of urban popular music both established and emerging, and to examine its causes from broader musical, sociological and artistic perspectives. Rather than focus on particular forms, such as traditional folk music, rebetika, or the 'new wave' of the 1960s exemplified by the international success of composers such as Hadjidakis and Theodorakis, the conference set out to situate these traditions in a broader Greek context and also an explicitly international one, in this way building upon a growing trend (Bucuvalas 2019; Tragaki 2019).